A comparative study between closed interlocking intramedullary nailing and locking plate by minimally invasive plate-osteosynthesis in diaphyseal fracture of tibia - Musa, Mohammad; Asaduzzaman, Mohammad; Sobhan, Syed A.; Barman, Shamol C.; Almamun, Abdullah (International Journal of Research in Orthopaedics, 2025)
Background: Tibial shaft fractures are common and often lead to significant complications. This study aims to compare the efficacy of interlocking intramedullary nailing (IMN), and minimally invasive plate osteosynthesis (MIPO) in treating these fractures. The aim of the study was to compare the outcome between closed interlocking intramedullary nailing and locking plate by MIPO in diaphyseal fracture of tibia. Methods: This prospective, comparative observational study was conducted at the Department of Orthopaedic Surgery, M.A.G. Osmani Medical College Hospital, Sylhet, Bangladesh, from October 2019 to March 2021, enrolling 30 patients with closed diaphyseal tibial fractures. Participants were randomly assigned to group A (interlocking intramedullary nailing) or group B (locking plate by MIPO). Data were analyzed using statistical package for the social sciences (SPSS) version 25, with p<0.05 considered significant. Results: In a study of 30 patients with tibial fractures (group A: 15, group B: 15), group A had significantly shorter surgery times (105±17 versus 119±18 minutes, p=0.043) and achieved full weight-bearing earlier (93.3% versus 46.7% at 12 weeks, p=0.014). Both groups showed similar radiological union rates (93.3% versus 80.0%, p=0.598). Group A had more anterior knee pain (73.3% versus 0%, p=0.001), while group B had more wound infections (20.0% versus 6.7%, p=0.224). Functional outcomes were better in group A (93.3% excellent versus 66.7%, p=0.16). Conclusions: Closed interlocking intramedullary nailing and locking plate by MIPO both are equally effective procedures for treating tibial diaphyseal fractures.